New insights into the effects of Aspergillus oryzae administration during the transition period in Bubalus bubalis - Sameh A. Abdelnour; Walaa M. Essawi; Nasser Ghanem; Ibrahim T. El-Ratel; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Ahmed N. F. Neamat-Allah; Shimaa A. Amer; Simon J. Davies; Ali Ali El-Raghi (Italian Journal of Animal Science)
The transition period is often associated with metabolic disorders in Bubalus bubalis. We examined the potential effect of Aspergillus oryzae (ASG) on blood biochemistry, adaptive immunity, milk yield and composition, dry matter intake, inflammation markers, and oxidative stress in buffalo cows. Thirty buffalo cows were divided into two homogeneous experimental groups (15 buffalo cows in each group) from 3 weeks pre-partum to 3 weeks post-partum. The first group received the basal diet and served as a control, while the second group was orally administered with 5 g of ASG per head per day. ASG treatment significantly improved liver and kidney functions. The concentration of haptoglobin, tumour necrosis factor-alpha (TNF-α), and Malondialdehyde (MDA) was significantly lower in the treated group (4.42 mg/dl, 68.89 pg/ml, 3.46 nmol, respectively) than in the control group (8.29 mg/dl, 83 pg/ml, 6.23 nmol, respectively). At the same time, the levels of catalase (CAT), glutathione peroxidase (GPx), immunoglobulin M, and G were significantly higher. Regarding energy metabolism, the ASG supplementation significantly increased total cholesterol, triglycerides, and high-density lipoprotein compared to the control group. Meanwhile, beta-hydroxybutyrate (BHB), non-esterified fatty acids (NEFA), and somatic cell counts in milk (SCC) were significantly reduced by ASG supplementation. The daily milk yield and its composition were significantly increased by the ASG supplementation (p < 0.001). In conclusion, the oral administration of 5 g ASG/ head/ day during the transition period improved milk yield, health status, and adaptive immunity in lactating buffalo cows. Additionally, it decreased inflammation and oxidative stress pathways.